(untitled) (Annals of Medical Research, 2021)
Aim: Many plants and plant originated products cause poisonings in children in Turkey. This study aims to study 23 plant-derived poisoning cases admitted to Inonu University, Turgut Ozal Medical Center, Pediatrical Emergency Service in terms of agents of toxication and the clinical features in order to decrease the number of poisonings.